A escolarização do sudoeste do Paraná entre 1890 e 1930 - Bido, Fábio Júlio (2021)
This research is articulated with the research line Society, Knowledge, and Education, from the Graduate Program in Education at the State University of West Paraná - Francisco Beltrão Campus and aimed to understand the schooling process in the Southwest region of Paraná between 1890 and 1930. In this sense, we chose as problematic, to explain the existence of Public Education in the region and how education was organized during the selected period. For the construction of this research, we used documentary and bibliographical sources, which bring data related to education in the region. We searched for information regarding teachers, students, number of schools, in which towns and cities, number of enrollments and other information relevant to the research theme, which is still little studied. The documents we analyzed were Reports, Government Messages, School Maps, official letters and other miscellaneous documents that contain some information about education in the region. We justify a time frame, considering the Proclamation of the Republic (1890) and which extends until 1930, the year of Getúlio Vargas' accession to power. This period was quite troubled in the region with the dispute for territory between Brazil and Argentina and later between Paraná and Santa Catarina, explained in the Contestado conflict. From the analysis carried out in this research, we were able to bring up social issues, migrations, local conflicts, ideologies that influenced the construction of the subjects of the time and, consequently, the education of these individuals in the region. We were able to analyze documents that portray since 1890 that Public Instruction in the Southwest region was present. The documents show numbers, a list of schools, students and teachers, and also point out the difficulties faced, the exposed needs of the teachers, the needs of the students, the structure of the schools, the resistance of parents, among many topics covered. Despite having encountered some barriers to gaining access to the documents, what we have achieved gives a very consistent basis for the events that took place at the time. With these documents, we register the regional history, serving as support, vestiges, and testimonies of the existence of schooling in the region.